2021
DOI: 10.1038/s41598-021-85592-w
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of anaerobic bacteria in cystic fibrosis lung using culture dependant and independent approaches

Abstract: Strict anaerobes are undeniably important residents of the cystic fibrosis (CF) lung but are still unknowns. The main objectives of this study were to describe anaerobic bacteria diversity in CF airway microbiota and to evaluate the association with lung function. An observational study was conducted during eight months. A hundred and one patients were enrolled in the study, and 150 sputum samples were collected using a sterile sample kit designed to preserve anaerobic conditions. An extended-culture approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Second, we cannot exclude that the limited detection of slow-growing or anaerobic bacteria may result from technical limitations inherent to the conventional culture-based approach. We did not want to change frameworks for sampling by the physicians, so we did not use any collecting device that could ensure the preservation of an anaerobic atmosphere for the sputa until processing in the laboratory ( Lamoureux et al, 2021 ). Moreover, we did not compare our results obtained by culture methods with sequencing-based data, as we only focused on culture methods applicable in most clinical microbiology laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we cannot exclude that the limited detection of slow-growing or anaerobic bacteria may result from technical limitations inherent to the conventional culture-based approach. We did not want to change frameworks for sampling by the physicians, so we did not use any collecting device that could ensure the preservation of an anaerobic atmosphere for the sputa until processing in the laboratory ( Lamoureux et al, 2021 ). Moreover, we did not compare our results obtained by culture methods with sequencing-based data, as we only focused on culture methods applicable in most clinical microbiology laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…Employing cultureindependent approaches, anaerobes have now been shown to be key members of the CF airway microbiome. Up to 91.1% of CF sputa have been shown to be positive for at least one anaerobic bacterial species [179]. Anaerobes are increasingly dominant in patients with better lung function [95], and several studies have reported the negative impact of antibiotics on anaerobic populations in the CF airway [87,89,104,105].…”
Section: Anaerobes Impact P Aeruginosa Antibiotic Resistancementioning
confidence: 99%
“…Fifty isolates of Prevotella melaninogenica cultured from sputum of 50 PWCF collected at the Western Brittany CF center (Roscoff, France) have been included in this study. Cultural methods from sputum (three different media, 21 days of culture at 37 • C in anaerobic atmosphere) have been previously described [5]. These 50 isolates have been identified by matrix-assisted laser desorption/ionisation time-of-flight mass spectrometry (MALDI-TOF MS Biotyper MBT) (Bruker, Billerica, MA, USA); a score of ≥ 2.0 was considered as accurate species-level identification; a score ≥ 1.7 but < 2.0 as a probable genus-level identification; a score < 1.7 as "unidentified".…”
Section: Clinical Isolates and Antibiotic Susceptibility Testingmentioning
confidence: 99%
“…The importance and abundance of strict anaerobic bacteria in the respiratory microbiota of people with cystic fibrosis (PWCF) is now established. These recent data are based on high-throughput sequencing [1,2] and cultural techniques [3][4][5]. Anaerobes colony count has been evaluated between 1.10 4 to 9.10 7 colony forming units per milliliter in sputum culture [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation